A Mixed Complementarity Model of Hydrothermal Electricity Competition in the Western United States - Bushnell, James (Operations Research, 2003)
This paper presents a modeling framework for analyzing competition between multiple firms that each possess a mixture of hydroelectric and thermal generation resources. Based upon the concept of a Cournot oligopoly with a competitive fringe, the model characterizes the Cournot equilibrium conditions of a multiperiod hydrothermal scheduling problem. Using data from the western United States electricity market, this framework is implemented as a mixed linear complementarity model. The results show that some firms may find it profitable to allocate considerably more hydro production to off-peak periods then they would under perfect competition. This strategy is a marked contrast to the optimal hydroschedules that would arise if no firms were acting strategically. These results highlight the need to explicitly consider profit-maximizing behavior when examining the impact of regulatory and environmental policies on electricity market outcomes.